Vegetable Oils and Hibiscus rosa-sinensis Leaf Extract in Solid Soap Formulation - Marliandi Tamo Ama; Ahmadi; Hulyadi; Baiq Risni Maripa; Yusran Khery (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study identified the effects of vegetable oil formulation and Hibiscus rosa-sinensis leaf extract concentration on the physicochemical quality of laboratory-scale solid soap. A 3 x 4 factorial design was used, consisting of three oil bases (A1, A2, and A3) prepared from coconut, olive, and palm oils and four extract concentrations (0, 1, 2, and 3%). The measured parameters were pH, moisture content, foam height, foam stability, organoleptic acceptance, and UV-Vis maximum wavelength of selected extract-containing soaps. The pH of all samples ranged from 9.00 to 9.43, indicating an alkaline soap system consistent with saponification. Moisture content varied from 11.00 to 19.00%; several samples met the 15% moisture criterion, while F1 and F4 exceeded it. Foam stability ranged from 74.96 to 88.89%, and foam height ranged from 0.33 to 1.33 cm. The A3 oil base showed the lowest mean moisture content (12.33%) and the highest mean foam stability (84.77%). Organoleptic evaluation indicated that F5 was the most preferred sample, whereas F11 was selected as the strongest technical candidate because it contained 2% extract, had the lowest moisture content, and showed the highest foam stability. UV-Vis analysis of A3 extract-containing soaps showed lambda max values of 374-377 nm with absorbance values of 0.747-0.751, supporting the persistence of flavonoid-related absorption in the soap matrix. The findings indicate that vegetable oil composition and H. rosa-sinensis leaf extract concentration influence solid soap quality and should be optimized jointly.